METHODS FOR DEVELOPING EMOTIONAL INTELLIGENCE IN STUDENTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article presents ideas on the importance of targeted, systematic work by teachers on the development of emotional intelligence, such work not only contributes to the personal development of students, but also increases the quality of general education, since emotional intelligence creates the basis for the psychological well-being of students and prevents the spread of negative phenomena such as bullying, deviant, aggressive and self-aggressive behavior, conflicts, child abuse, etc.